The Role of Insurance in Ensuring the Financial Sustainability of the Population (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
The article analyzes the role and importance of the insurance system in ensuring the financial stability of the population. In particular, the methods of risk management, solvency and reduction of personal financial risks through insurance services are considered. The article discusses the development trends of the insurance market, as well as mechanisms for providing affordable and convenient insurance for the population. This study offers systematic approaches to increasing the financial security of the population and creating appropriate insurance services for them.